Man, medicine and the state : the human body as an object of government sponsored medical research in the 20th century ; [Conference on Man, Medicine and the State: the Human Body as an Object of Government Sponsored Research, 1920 - 1970, Heidelberg, October 2003] - Eckart, Wolfgang U. 1952-2021 Hrsg; Conference on Man, Medicine and the State: the Human Body as an Object of Government Sponsored Research, 1920 - 1970 (Beiträge zur Geschichte der Deutschen Forschungsgemeinschaft, 2006)
Preface -- Introduction / Wolfgang U. Eckart -- "You should not use our Senegalese infantrymen as guinea pigs" : human vaccination experiments in the French army, 1916-1933 / Christian Bonah -- First principles : Julius Moses and medical experimentation in the late Weimar Republic / Wolfgang U. Eckart, Andreas Reuland -- Nutritional physiology in the "Third Reich" 1933-1945 / Alexander Neumann -- Pervitin (Metamphitamine) tests, use and misuse in the German Wehrmacht / Peter Steinkamp -- Funding the scientific foundations of race policies : Ernst Rüdin and the impact of career resources on pyschiatric genetics, ca. 1910-1945 / Volker Roelcke -- The Deutsche Forschungsgemeinschaft (German Research Found) and the "backwardness" of German human genetics after World War II : scientific controversy over a proposal for sponsoring the discipline / Anne Cottebrune -- Flying bodies, enforcing states : German aviation medical research from 1925 to 1975 and the Deutsche Forschungsgemeinschaft / Karl Heinz Roth -- Otto Bickenbach's human experiments with chemical warfare agents and the concentration camp Natzweiler / Florian Schmaltz -- Disregard for human life : hypothermia experiments in the Dachau concentration camp / Wolfgang U. Eckart, Hana Vondra -- Barbaric research, Japanese human experiments in occupied China : relevance, alternatives, ethics / Till Bärnighausen -- From deputy to "Reichsbevollmächtiger" and defendant at the Nuremberg medical trials : Dr. Kurt Blome and cancer research in National Socialist Germany / Gabriele Moser -- German malariology experiments with humans, supported by the DFG until 1945 / Marrion Hulverscheidt -- From medical war crimes to compensation : the plight of the victims of human experiments / Paul Weindling -- The Tuskegee syphilis experiment / James H. Jones -- Darkened by the shadow of the atom : burn research in 1950s America / Susan E. Lederer -- Back to first principles : First World research in Third World countries / David Rothman -- Contributors -- Register